Study on the shielding materials for low-energy gamma sources - Aminordin Sabri, A.H.; Abdul Aziz, M.Z.; Olukotun, S.F.; Tabbakh, F.; Tajudin, S.M. (2020)
Photon dosimetry is indispensable in designing an irradiation facilities shielding. Monte Carlo simulation was utilized to investigate the efficiency of relatively new developed clay and Gadolinum (Gd)-doped polymer as a radiation shielding material for low energy gamma sources (Am- and Co-). The calculated linear attenuation coefficient () of Am- and Co- for clay is higher within . % and . % compared to ordinary concrete, respectively. The value for Gd-doped polymer is higher by a factor of and compared to clay for Am- and Co-, respectively. A thickness of cm and cm from both clay and concrete were adequate to attenuate almost % incident photons from Am- and Co-, respectively. The same thickness of cm by Gd-doped polymer could attenuate almost % of Co- photons. cm thickness of clay and concrete could shield the gamma source dose rate of Am- ( MBq) down to . Sv/hr, while almost cm needed for Co- source. Gd-doped polymer with thickness of cm could shield almost % the dose rate from Co- source. For higher energy gamma sources, clay and ordinary concrete need to be doped with a higher Z element to ensure safety of the radiation.